Developing a Character Education Model Based on Riyadhus Shalihin in an Islamic Senior High School - Bamualim; sadiyahh, Maemunah; Indra, Hasbi (TA`DIBUNA, 2026)
Character education is the main foundation for shaping students’ character in Islamic schools; however, the modern educational context requires a model that is not only normative but also practical. This study aims to develop a character education model based on the Book of Riyadhush Shalihin at SMA Babussalam Assunnah Depok through intracurricular, cocurricular, and extracurricular activities. The study employs a qualitative approach through library research and fieldwork, using interviews and on-site observations involving the principal, teachers, and mentors. Data were analyzed using the ADDIE model and thematic analysis. The findings show that character education at this school is integrative and sustainable, with the internalization of Islamic values occurring through classroom instruction, religious habituation, teacher role modeling, and direct experiences in various school activities. The study concludes that the Riyadhush Shalihin–based character education model is contextual, effective, and has strong potential to be implemented in other Islamic schools.